The Influence of Implementation and Financial Management on Village Financial Performance (A Study in the Villages of Lolayan Subdistrict, Bolaang Mongondow Regency) - Pongayo, Annisa; Blongkod, Harun; Pakaya, Lukman (Nomico, 2024)
Several factors impact the effectiveness of financial management in village governments, as stated in Bolaang Mongondow Regent Regulation No. 4 of 2019. These factors include preparation, allocation, execution, oversight, and responsibility. The main objective of this study is to determine whether administration and execution significantly affect the financial performance of villages in the Lolayan District of Bolaang Mongondow Regency. Quantitative research methods, which involve numerical and statistical techniques, were used. Secondary data was collected through surveys, interviews, and literature reviews. A total of 133 samples were used for this study. The applied theory is agency theory, which helps understand the interaction between principals (those with an interest) and agents (those who act on their behalf). The research findings suggest that implementation does not significantly impact the financial performance of villages in the Lolayan District. This may be due to various factors, including a lack of transparency in the allocation of village funds and the treasurer's inability to adjust program implementation according to current regulations. Consequently, many activities funded by the village fund lack the necessary proof documents or receipts.